PENGELOLAAN SAMPAH DENGAN KONSEP 3R DI KOTA SAMARINDA - Wijaya, Doni; Suyatni, Andi; Apriyani, Apriyani (Jurnal Kesehatan dan Pengelolaan Lingkungan, 2024)
Waste refers to objects or substances that are no longer used and thrown away because they have no further function, such as packaging, dirt or leaves. In accordance with this definition, in Article 1 of Law Number 18 of 2008 concerning Waste Management, waste is defined as residue from daily human activities or the result of natural processes in solid form. According to the Ministry of Environment and Forestry in 2019, in 2018 it estimated 85,000 tons of waste, assuming an increase of 150,000 tons/day in 2025. This type of research uses qualitative methods with a case study research design. The main informants in this research were residents of RT 76, Sungai Pinang Dalam Village, Samarinda City, supporting informants were the Head of RT 76, Sungai Pinang Dalam Village and key informants at the Temindung Sanitarian Community Health Center, Sungai Pinang Dalam Village. The technique for selecting informants in this research is Purposive Sampling. Data analysis technique using Miles and Huberman theory, 2019. Residents of RT 76, Sungai Pinang Dalam Village, never implement reuse activities in their daily lives, residents of RT 76, Sungai Pinang Dalam Village, never implement reuse activities at home due to lack of waste management facilities and personnel. waste management officers, residents of RT 76 Sungai Pinang Dalam Subdistrict do not carry out recycling activities at home. From this research, it is hoped that the residents of RT 76 Sungai Pinang Dalam Village can implement waste management using the 3R concept.